Draft 11th Five Year Plan 2007-2012 and Annual Plan 2007-2008 Government of Mizoram - Planning Commission (Planning Commission, 2007)
Against the agreed outlay of Rs. 2300.01 crore for 10th Five Year Plan (2002-07), total of the successive five Annual Plans is Rs. 2969.52 crore and the anticipated expenditure is Rs. 3159.07 crore. There have been significant achievements in various sectors during the Tenth Plan period. Detail physical targets and achievements made have been enlisted in statement portion (Annexure- II).
Planning and Programme Implementation Department, Government of Mizoram